HeRO Graft: Indications, Technique, Outcomes, and Secondary Intervention - Tabriz, David M.; Arslan, Bulent (Seminars in Interventional Radiology, 2022)
The Hemodialysis Reliable Outflow (HeRO) graft is a nontraditional, surgical, and endovascularly placed access that offers options in failing arteriovenous fistula/arteriovenous graft or catheter-dependent patients. The HeRO graft provides a unique option and is specifically referred to in the 2019 Kidney Disease Outcomes Quality Initiative (KDOQI) vascular access update. The interventional radiologist has a role and opportunity to work collaboratively with surgeons in assisting with (1) the identification, selection, preparation for, and placement of HeRO grafts and (2) providing post-placement maintenance to ensure long-term patency.
Keywords: HeRO graft; hemodialysis; vascular access; central venous stenosis; interventional radiology